Barriers, biases, and beliefs about arteriovenous fistula placement in children: A survey of the International Pediatric Fistula First Initiative (IPFFI) within the Midwest Pediatric Nephrology Consortium (MWPNC). Issue 1 (28th May 2014) - Chand, Deepa H.; Geary, Denis; Patel, Hiren; Greenbaum, Larry A.; Nailescu, Corina; Brier, Michael E.; Valentini, Rudolph P.
Abstract There has been recent emphasis on increased arteriovenous fistula (AVF) use and decreased central venous catheter use in hemodialysis (HD) patients. The International Pediatric Fistula First Initiative was founded via collaborative effort with the Midwest Pediatric Nephrology Consortium to alert nephrologists, surgeons, and dialysis staff to consider fistulae as the best access in pediatric HD patients. A multidisciplinary educational DVD outlining expectations and strategies to increase AVF placement and usage in children was created. Participants were administered a survey previewing and postviewing to identify barriers to placement and usage of AVF in children. A total of 52 surveys were subdivided as either "dialysis staff" or "proceduralist" at five centers. Thirty‐three percent of respondents were unaware if their practice was following published guidelines. Sixty‐five percent of respondents stated they referred to a dedicated vascular access surgeon at their respective institutions. Methods used to monitor AVF function included physical exam, venous pressure monitoring, and ultrasound dilution. Vascular access was placed within 3 months in only 35% of patients. Interdisciplinary communication problems between surgeons, interventional radiologists, and nephrologists were identified as a major barrier. Lack of AVF usage was often due to maturation failure. Routine access rounds did not occur in any centers. Regarding monitoring, 74% of the respondents use physical exam, 26% use venous pressure monitoring, and 9% use ultrasound dilution. Ninety‐three percent of dialysis staff stated they would change practice patterns following the intervention; however, 12% of surgeons stated they would alter practice patterns. To our knowledge, this is the first report to identify barriers to placement of AVF in children from the perspectives of multidisciplinary team members including pediatric nephrologists, surgeons, interventional radiologists, and multidisciplinary dialysis staff.